Primary and mental health service use in community health center patients before and after cancer diagnosis. (28th April 2022) - Larson, Annie E.; Angier, Heather; Suchocki, Andrew; Voss, Robert W.; Marino, Miguel; Warren, Nathaniel; Huguet, Nathalie
Abstract: Background: Cancer survivors face increased risk for chronic diseases resulting from cancer, preexisting conditions, and cancer treatment. Having an established primary care clinic or health insurance may influence patients' receipt of recommended preventive care necessary to manage, treat, or diagnose new conditions. This study sought to understand receipt of healthcare in community health centers (CHCs) before and after cancer diagnosis among cancer survivors. We also examined the type of care received and assessed whether being established with a CHC or the type of health insurance affected the use of services. Methods: Using electronic health record data and linked cancer registries from 5, 649 CHC patients in three states from 2012 through 2018, we obtained monthly rates of primary care and mental health/behavioral health (MHBH) visits and the probability of receipt of care before and after a cancer diagnosis. Results: Seventy‐five percent of CHC patients diagnosed with cancer returned to their primary CHC for care within 2‐years of their diagnosis. Among those who returned, there was a sharp increase in primary and MHBH care shortly before their diagnosis. Significantly more primary care (pre: 19.6%, post: 21.9%, p < 0.001) and MHBH care (pre: 1.2%, post: 1.6%, p < 0.001) was received after diagnosis than before. However, uninsured patients had fewer visits after their diagnosis than before. Conclusion: Use of preventive care for cancer survivors is particularly important. Having an established primary care clinic may help to ensure survivors receive recommended screening and care. Abstract : In this study on the receipt of preventive healthcare among community health center patients before and after a cancer diagnosis, we found that significantly more primary and mental healthcare was received after diagnosis than before. However, uninsured patients had fewer visits after their diagnosis than before.